How motivation enables polyglots to acquire foreign languages - Sofyan, Zulkhairi; Fajri, Akmal; Sumardi, Sumardi; Zulhelmi, Anshar; Shaliha, Chairunnisa Ahsana Amalan; Yasir, Muhammad (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
This study investigates the motivation of polyglots to learn multiple languages, a topic not extensively studied in literature. It focuses on the role of motivation as a stimulus triggering consistent behavior in learning a foreign language, offering a unique perspective on this phenomenon. Purpose: The present study examines the diverse motivational backgrounds of polyglots and investigates the relationship between these motivations and the multilingual acquisition of foreign languages by polyglots. The study involved five informants who participated in semi-structured interviews, utilizing a descriptive case study approach for data collection. Results: The results demonstrated that the four main reasons why polyglots learned numerous foreign languages were: (a) enjoyment; (b) social interaction; (c) career advancement; and (d) intellectual pursuits. Prior studies have mostly shown that people who are studying foreign languages do so primarily for academic, professional, and social reasons. Apart from the three reasons, polyglots learned multiple languages for their own enjoyment. This is the main justification for their dedication to long-term multilingual education. Conclusion: The results of this study advance our knowledge of the motivations behind multilingual polyglots' acquisition of foreign languages. It is envisaged that language learners will successfully acquire numerous foreign languages by adopting or modifying the research participants' motives. To sustain kids' desire to learn foreign languages, educators, parents, and policymakers can think about, select, and construct engaging language activities as well as appropriate language teaching approaches.